ARE TECHNOLOGY AIDS STILL USED IN ELT AFTER THE PANDEMIC?(TEACHERS’ POV) - Mandasari, Yuyun Putri; Wulandari, Eka (Pedagogic Research-Applied Literacy Journal, 2025)
During the pandemic, technology and software use is inevitable for teachers and students due to the safety and sake of health. All traditional classrooms were shifted into online methods in which the learning process must be taken at home. Dealing with this, various educational platforms to support online learning was offered, impacting many problems the teachers and students faced. So, what about now, in the post-pandemic era? Did the teachers still use technology aids and software to support the English learning process in the face-to-face classroom and what are the challenges?. This study aimed to determine whether technology and online platforms for educational support, such as Zoom Cloud Meeting, Google Classroom, YouTube, Social Media, and Learning Applications were still used after the pandemic. English teachers in Trenggalek Regency were used as the sample of this study and a questionnaire was distributed online to collect the data. The survey research was employed since it was attempted to take data from individuals who took part in this research.